Effects of early child-care on cognition, language, and task-related behaviours at 18 months: an English study. - Sylva, K; Stein, A; Leach, P; Barnes, J; Malmberg, L (2011)
This study investigated the effects of different characteristics of early child-care in England on the development of cognition, language, and task-related attention and behaviour (orientation/engagement and emotion regulation during the Bayley assessment) at 18 months. Data were drawn from a prospective longitudinal study of 1,201 infants. As found in previous studies, socio-demographic characteristics and maternal caregiving (especially 'opportunities for stimulation') were significant predictors of all child outcomes. There were also effects of quantity of individual and group care, and quality of non-maternal care. Controlling for demographics and maternal caregiving, more hours of group care (nurseries) were related to higher cognitive scores, while more hours of individual care (e.g., grandparents, nannies etc.) were related to lower orientation/engagement scores. Non-maternal caregiving was observed in a subsample of 345 children, and after controlling for all covariates as well as quantity and stability of care, quality of care was found to be predictive of higher cognitive ability and better orientation/engagement. Although the effect sizes were small in magnitude, in line with other similar studies, such modest effects from a large English sample are important when viewed in light of the widespread use of non-maternal care during infancy and early childhood.